The Psychology of Effective Studying: How to Succeed in Your Degree, 1st edition - Penn, Paul (Routledge, 2020)
This book provides a vital guide for students to key study skills that are instrumental in success at university, covering time management, academic reading and note-taking, academic integrity, preparation of written assignments, teamwork and presentations.